UPAYA GURU MENGEMBANGKAN KREATIVITAS ANAK PRA SEKOLAH MELALUI MEDIA PLAYDOUGH DIKELOMPOK B KOBER MIFTAHUL FALAH - Yayu Rahayu; Yeni Heryani (IKIP Siliwangi, 2019)
Creativity has a very important role in the lives of children. Through kerativitas, children can be creative in accordance with the talent or ability, the child can solve a problem and can improve the quality of life in the future. Therefore, stimulation is needed that can develop the creativity of children, one of them through mengguanaan media playdough. In early childhood creativity has not developed well, early childhood has not been smooth in expressing idea idea idea. The purpose of this assessment is to describe the level of early childhood creativity by applying playdough media, differences in early childhood creativity levels before and after applying media playdough. Methods used in this study are classroom action research methods (PTK). The subjects of this study were children aged 4-5 years kober miftahul falah which amounted to 14 children consisting of 9 women and 5 men. The results of this study indicate a positive impact in improving creativity of children by 25.83% based on evaluation results from cycle I and cycle II.Dengan, it can be concluded that the media playdough provide a significant influence. So that can be recommended for teachers to use media playdough can be used as an alternative to develop creativity in children effectively. For schools to be able to facilitate by providing other learning media that can enhance the creativity of young children.